Investigating the causal relationship between inflammation and multiple types of hearing loss: a multi-omics approach combining Mendelian randomization and molecular docking - Zhang, Jingqi; Guo, Tao; Chen, Yaxin; Wang, Xiangjin; Wu, Lijiao; Xie, Hui (Frontiers in Neurology, 2024)
BackgroundHearing loss affects over 10% of the global population. Inflammation is a key factor in hearing loss caused by noise, infection, and aging, damaging various hearing-related tissues (e.g., spiral ligament, stria vascularis). Mendelian randomization (MR) can help identify potential causal relationships and therapeutic targets.MethodsWe conducted MR analyses on 91 inflammatory proteins (n = 14,824) and genome-wide association study results for various hearing loss types in European ancestry populations, including sensorineural hearing loss (SNHL; ncases = 15,952, ncontrols = 196,592), sudden idiopathic hearing loss (SIHL; ncases = 1,491, ncontrols = 196,592), and other hearing loss (OHL; ncases = 4,157, ncontrols = 196,592). Additionally, hearing loss with difficulty in hearing (ncases = 14,654, ncontrols = 474,839) served as a validation set. To predict inflammatory protein-enriched pathways and tissues, we performed enrichment analysis, functional annotation, and tissue analyses using “OmicsNet2.0” and “FUMA” platforms. We also combined “CoreMine” and molecular docking to explore potential drugs targeting inflammatory proteins and investigate binding efficacy.ResultsCCL19 was identified as a common risk factor for SNHL and OHL, which was validated in the hearing loss with difficulty in hearing dataset. Tissue analysis revealed that SIHL-related inflammatory proteins were enriched in the amygdala. Multi-omics research indicated associations between inflammatory proteins and neurodegenerative diseases. Molecular docking studies suggested that Chuanxiong Rhizoma and Uncariae Ramulus Cumuncis are potential drugs for targeting CCL19.ConclusionThis study identified CCL19 as a common risk factor for various types of hearing loss through MR analysis, highlighting the crucial role of inflammatory proteins in hearing loss. The enrichment of related inflammatory proteins in the amygdala and their association with neurodegenerative diseases provide new insights into the mechanisms of hearing loss.